Recent advances in immunotherapy and its combination therapies for advanced melanoma: a review - Xu, Jiamin; Mu, Shukun; Wang, Yun; Yu, Suchun; Wang, Zhongming (Frontiers in Oncology, 2024)
The incidence of melanoma is increasing year by year and is highly malignant, with a poor prognosis. Its treatment has always attracted much attention. Among the more clinically applied immunotherapies are immune checkpoint inhibitors, bispecific antibodies, cancer vaccines, adoptive cell transfer therapy, and oncolytic virotherapy. With the continuous development of technology and trials, in addition to immune monotherapy, combinations of immunotherapy and radiotherapy have shown surprising efficacy. In this article, we review the research progress of immune monotherapy and combination therapy for advanced melanoma, with the aim of providing new ideas for the treatment strategy for advanced melanoma.